Synthesis, kinetic mechanism and docking studies of vanillin derivatives as inhibitors of mushroom tyrosinase. Issue 17 (1st September 2015) - Ashraf, Zaman; Rafiq, Muhammad; Seo, Sung-Yum; Babar, Mustafeez Mujtaba; Zaidi, Najam-us-Sahar Sadaf
Graphical abstract: Abstract: The purpose of the present study was to discover the extent of contribution to antityrosinase activity by adding hydroxy substituted benzoic acid, cinnamic acid and piperazine residues to vanillin. The study showed the transformation of vanillin into esters as shown in (4a –4d ), (6a –6b ), and (8a –8b ). In addition, the relationship between structures of these esters and their mushroom tyrosinase inhibitory activity was explored. The kinetics of inhibition on mushroom tyrosinase by these esters was also investigated. It was found that hydroxyl substituted benzoic acid derivatives were weak inhibitors; however hydroxy or chloro substituted cinnamic acid and piperazine substituted derivatives were able to induce significant tyrosinase inhibition. The mushroom tyrosinase (PDBID2ZWE ) was docked with synthesized vanillin derivatives and their calculated binding energies were compared with experimental IC50 values which provided positive correlation. The most potent derivative 2-(4-formyl-2-methoxyphenoxy)-2-oxoethyl (2 E )-3-(4-hydroxyphenyl)prop-2-enoate (6a ) possesses hydroxy substituted cinnamic acid scaffold having IC50 value 16.13 μM with binding energy of −7.2 kcal/mol. The tyrosinase inhibitory activity of (6a ) is comparable with standard kojic acid. Kinetic analysis indicated that compound6a was mixed-type tyrosinase inhibitor with inhibition constant values K i (13 μM) and K i ′ (53 μM) and formed reversible enzyme inhibitor complex. The active vanillin analog (6a ) was devoid of toxic effects as shown in cytotoxic studies.